Neutrophil migration induced by IL-1β depends upon LTB4 released by macrophages and upon TNF-α and IL-1β released by mast cells - Oliveira, Sandra Helena Penha de [UNESP]; Canetti, C.; Ribeiro, R. A.; Cunha, F. Q. (Springer Nature, 2008)
In the present study, we investigate whether mast cells and macrophages are involved in the control of IL-1β-induced neutrophil migration, as well as the participation of chemotactic mediators. IL-1β induced a dose-dependent neutrophil migration to the peritoneal cavity of rats which depends on LTB 4, PAF and cytokines, since the animal treatment with inhibitors of these mediators (MK 886, PCA 4248 and dexamethasone respectively) inhibited IL-1β-induced neutrophil migration. The neutrophil migration induced by IL-1β is dependent on mast cells and macrophages, since depletion of mast cells reduced the process whereas the increase of macrophage population enhanced the migration. Moreover, mast cells or macrophages stimulated with IL-1β released a neutrophil chemotactic factor, which mimicked the neutrophil migration induced by IL-1β. The chemotactic activity of the supernatant of IL-1β-stimulated macrophages is due to the presence of LTB4, since MK 886 inhibited its release. Moreover, the chemotactic activity of IL-1β-stimulated mast cells supernatant is due to the presence of IL-1β and TNF-α, since antibodies against these cytokines inhibited its activity. Furthermore, significant amounts of these cytokines were detected in the supernatant. In conclusion, our results suggest that neutrophil migration induced by IL-1β depends upon LTB4 released by macrophages and upon IL-1β and TNFα released by mast cells. © 2007 Springer Science+Business Media, LLC.
Keywords: IL-1β; LTB4; Mast cells; Neutrophil migration; TNF-α; 1,4 dihydro 2,4,6 trimethyl 3,5 pyridinedicarboxylic acid methyl 2 phenylthioethyl ester; 3 [3 tert butylthio 1 (4 chlorobenzyl) 5 isopropyl 2 indolyl] 2,2 dimethylpropionic acid; dexamethasone; interleukin 1beta; leukotriene B4; thrombocyte activating factor; tumor necrosis factor alpha; animal cell; animal experiment; cell stimulation; concentration response; controlled study; macrophage; male; mast cell; neutrophil; neutrophil chemotaxis; nonhuman; peritoneal cavity; protein analysis; protein function; protein secretion; rat; Animals; Anti-Inflammatory Agents; Arachidonate 5-Lipoxygenase; Cell Movement; Interleukin-1beta; Leukotriene B4; Macrophages; Macrophages, Peritoneal; Male; Mast Cells; Models, Biological; Neutrophils; Rats; Rats, Wistar; Tumor Necrosis Factor-alpha; Animalia; Rattus